Sensitive electrochemical detection of bisphenol A at screen-printed graphite electrode modified with nitrogen-doped graphene sheets - Sakineh Esfandiari Baghbamidi (Journal of Electrochemical Science and Engineering, 2021)
A novel voltammetric sensor was developed by modifying screen-printed graphite electrode (SPGE) with nitrogen doped graphene sheets (N-GSs) to detect bisphenol A. The electrochemical results exhibited that N-GSs / modified SPGE has high sensing performance towards the oxidation of bisphenol A. Excellent results were obtained for bisphenol A detection in the linear range from 0.08 to 300.0 µM with a sensitivity of 0.1626 µA µM-1 and limit of detection of 0.02 µM. Also, the fabricated N‑GSs/SPGE sensor showed good stability. The as-prepared sensor was tested towards the detection of bisphenol A in real samples. The measured results established the great sensing ability of N-GSs/SPGE for bisphenol A with high selectivity and good stability in real samples.